PENENTUAN PRESISI DAN BIAS METODE PENGUJIAN AIR DAN AIR LIMBAH MELALUI UJI BANDING ANTAR LABORATORIUM - Anwar Hadi (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2008)
Determination of method precision and bias for testing of water and wastewater can be conducted by inter-laboratorycomparison. Performance evaluation sample was determined by provider as assign value and distributed toparticipants. The assign value is used as comparison with laboratory result and grand mean is calculated to determinemethod bias. The method precision is determined by standard deviation from result of all laboratories participantdivided by grand mean. The result of inter-laboratory comparison for testing of SO42- showed that methodprecision 5.4% and method bias 0.3% for assign value 19.9 mg/l. On the other hand, the standard methods for theExamination of water and wastewater showed that the method precision and bias for SO42- are 1.7% and 9% for assignvalue 7.45 mg/l. For testing of Cl- in water and wastewater, the result of inter-laboratory comparison gave methodprecision and bias 7.4% and 2.1% for assign value 29.5 mg/l. The method precision and bias from the StandardMethods are 4.2% and 1.7% with assign value 241 Cl-/l. Furthermore, the method precision from the standardmethods for COD is 5.6% with assign value 195 mg/l and method precision from the result of inter-laboratorycomparison is 6.4%, method bias 3.4% with assign value 194 mg/l. The participant of inter-laboratory comparisonprogram could comply with the standard methods for testing of SO42-, Cl-, COD in water and waste water.